2016
DOI: 10.1007/s00018-016-2244-8
|View full text |Cite
|
Sign up to set email alerts
|

GH13 amylosucrases and GH70 branching sucrases, atypical enzymes in their respective families

Abstract: Amylosucrases and branching sucrases are α-retaining transglucosylases found in the glycoside-hydrolase families 13 and 70, respectively, of the clan GH-H. These enzymes display unique activities in their respective families. Using sucrose as substrate and without mediation of nucleotide-activated sugars, amylosucrase catalyzes the formation of an α-(1 → 4) linked glucan that resembles amylose. In contrast, the recently discovered branching sucrases are unable to catalyze polymerization of glucosyl units as th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
72
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 50 publications
(72 citation statements)
references
References 136 publications
0
72
0
Order By: Relevance
“…KEYWORDS GH70 enzymes, glucansucrase, branching sucrase, insoluble glucan, Leuconostoc mesenteroides, intermediate E nzymes of glycoside hydrolase family 70 (GH70) are increasingly attracting attention for their potential in producing ␣-glucans with wide applications in food and feed products, as well as health care products (1-3). GH70 enzymes are structurally and mechanistically related to the GH13 (4, 5) and GH77 (4, 6) families, with which they form the GH-H clan (4,6) of glycoside hydrolases (5,7,8). To date, a total of 66 GH70 enzymes have been biochemically characterized, most of which are distributed in the genera Lactobacillus, Leuconostoc, Streptococcus, and Weissella (http://www.cazy.org/GH70 _characterized.html) (9).…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…KEYWORDS GH70 enzymes, glucansucrase, branching sucrase, insoluble glucan, Leuconostoc mesenteroides, intermediate E nzymes of glycoside hydrolase family 70 (GH70) are increasingly attracting attention for their potential in producing ␣-glucans with wide applications in food and feed products, as well as health care products (1-3). GH70 enzymes are structurally and mechanistically related to the GH13 (4, 5) and GH77 (4, 6) families, with which they form the GH-H clan (4,6) of glycoside hydrolases (5,7,8). To date, a total of 66 GH70 enzymes have been biochemically characterized, most of which are distributed in the genera Lactobacillus, Leuconostoc, Streptococcus, and Weissella (http://www.cazy.org/GH70 _characterized.html) (9).…”
mentioning
confidence: 99%
“…To date, a total of 66 GH70 enzymes have been biochemically characterized, most of which are distributed in the genera Lactobacillus, Leuconostoc, Streptococcus, and Weissella (http://www.cazy.org/GH70 _characterized.html) (9). Crystallographic structures of these enzymes suggested that they adopt a unique U-shaped fold organized into five distinct structural domains, i.e., A, B, C, IV, and V (10)(11)(12), of which A, B, and C are shared by GH13 enzymes, suggesting an evolutionary relationship between these two families (5).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…[23][24][25] Of the GSs, dextransucrases (DS; E.C. 2.4.1.5; CAZy family GH70) catalyse the synthesis of dextrans that are α-glucans of molar masses ranging from 10 4 to 10 9 g mol −1 with at least 50% α(1 → 6) linkages and various branching points.…”
Section: Introductionmentioning
confidence: 99%
“…33,34 In addition to polymer formation, GSs can also transfer the glucosyl unit of sucrose to a large variety of carbohydrate acceptors, including mono-, di-and trisaccharides such as galactose, xylose, maltose, isomaltose, mannose, maltotriose, panose, cellobiose, nigerose, lactose, raffinose and melibiose, as well as aglycon molecules such as polyols or flavonoids. 25,[35][36][37][38][39] However, there are very few publications describing the glucosylation using GSs of oligosaccharides with a DP higher than 3. The first example of this involved the strict elongation of maltooligosaccharides (MOSs) with a DP between 2 and 8 by the GTF-I and GTF-S enzymes from S. mutans 6715 40 and the dextransucrase from L. mesenteroides NRRL B-512FM.…”
mentioning
confidence: 99%